HPLC-HESI-MS/MS Analysis of Phenolic Compounds from Cynoglossum tubiflorus Leaf Extracts: An Assessment of Their Cytotoxic, Antioxidant, and Antibacterial Properties - Dhouha Dallali; Jawhar Fakhfakh; Cédric Paris; Nissaf Aoiadni; Stéphanie Philippot; Arnaud Risler; Mihayl Varbanov; Noureddine Allouche (Plants, 2024)
The current study aimed to investigate the chemical composition, antioxidant, antibacterial, and cytotoxic properties of three extracts (hexane, dichloromethane, and methanol) from Cynoglossum tubiflorus. The composition of the methanolic extract was elucidated using HPLC-HESI-MS/MS analysis. The antioxidant effect was examined using NO, DPPH, FRAP, and TAC assays. Antimicrobial activity was evaluated by broth microdilution using various bacterial strains such as S. aureus, S. epidermidis, P. aeruginosa, E. coli, and K. pneumoniae. Structural disruptions in Gram-positive bacteria were visualized using scanning electron microscopy (SEM). Cytotoxic effects were evaluated on human MRC-5 in culture according to the MTT assay. The outcomes suggest that methanol extract contained a high amount of phenolic compounds (254.35 ± 0.360 mg GAE/g DE and 211.59 ± 0.939 mg QE/g DE). By applying the HPLC-HESI-MS/MS analysis, 32 compounds were identified, including phenolic acids, flavonoids, lignans, and fatty acids. This extract showed strong antioxidant (IC50 = 0.043 ± 0.001 mg/mL) and antimicrobial (MIC = 156 µg/mL) activities. The SEM suggests that cells exhibited membrane distortions characterized by surface depressions and alterations in bacterial shape, including dents, when compared to untreated cells. The in vitro cytotoxicity effect on human MRC-5 cells showed no toxicity effects at a concentration of 600 µg/mL. In silico analysis predicted low toxicity for all tested compounds across four different administration routes. This research indicates that this plant could be explored as a powerful source of natural drugs to target pathogens, with applications in the food, pharmaceutical, and medical industries.